Evaluation, recommendation and implementation of the local hospital catering system. (13th November 2019) - Barocco, G; Germano, D; Patussi, V; Cella, M; Tiziana, L; Pernarcic, A; Occoni, E; Calabretti, A; Bogoni, P
Abstract: : According to the literature the prevalence of the risk of malnutrition o hospitalized people exceeds 25% of patients, this evidence is also related to low meal satisfaction. To reduce hospital malnutrition it is also important to improve the consumption of meals by implementing organoleptic and nutritional quality (O&NQ). The Local Health Agency of Trieste (ASUITS) has conducted surveys to find out how to evaluate and improve the procurement qualifications of hospital catering systems (HCS) and how to implement O&NQ. The production processes of meals served in two clinics using Cook Chill (CC) and Cook/Fresh - Hot Hold (CFHH) production process, respectively, were evaluated from 2017 - 2019. The Nutrient Analysis Critical Control Point process was applied for the evaluation of two catering systems. In addition, the antiradicalic power (ARP) of 120 samples of meals by the University of Trieste was analysed. In 2019 an investigation was conducted to compare the satisfaction and ARP content of meals served to patients in two hospital wards (N = 60). The meals to patients of two wards respectively with CC Cold Plating Retherm (PR) and CC Hot PR were served. Meals produced by the CC production process highlight the average loss of 50% of ARP compared to the CFHH. Meals produced by the CC Cold PR method limit the loss of ARP by 15-40% less compared to the CC Hot PR method. The satisfaction of patients who have consumed meals produced by the CC Cold PR method is double compared to that of patients who have consumed meals produced by the CC Hot PR method. The surveys have produced significant evidence to evaluate hospital meal production processes and to improve O&NQ. The results were used to develop recommendations for the drafting of tender specifications capable of also protecting nutritional variables. The evaluation of the O&NQ of HCS represents a central determinant of food safety and nutrition security and must be taken into consideration in the procurements procedure. Key messages: Hospital catering contracts must evaluate and guarantee organoleptic and nutritional quality. Integrated evaluation of organoleptic and nutritional quality is an integral part of hospital meals.